Hataw Subanen (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
This study aimed to identify the basic Subanen dance steps as the basis for creating an inspired Subanen dance exercise routine. Dance exercise is a well-known activity for all ages. People are passionate about doing it for them to stay fit and healthy. A descriptive method of research was used in the study in which the observation method was utilized. Purposive sampling was used to ensure the authenticity of the dance steps, which were from the true-blooded Subanen dancers. Three pairs of dancers, three musicians, and one key informant were the respondents of the study. Based on the interview and observation results, stamping or “pasagagang” steps is the basic footwork, and twisting or moving the hands and wrist circularly like doing the “kumintang”, the basic hand movement of the dance. Most of the Subanen dances are in 4/4-time signature with the counting of 1, 2, 3, & 4. Their dances usually start with slow movements, then gradually change from moderately fast to fast. “Agong” is the commonly used musical instrument in accompanying their dances. Five basic steps were identified: praise, grace, prayer, casting, and courtship. Based on the basic dance steps, a dance exercise routine called “Hataw Subanen” was created. Thus, exercise does not only use modern dance movements but also traditional or indigenous dances/movements. Hataw Subanen not only promotes a fit and healthy life, but also preserves, enhances, and harnesses one’s indigenous culture and tradition.